Analysis Tax Advantage of Financing Leverage: An Empirical Research (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research objective are analyze financial leverage advantage through analyze and discuss financial leverage cost, and achieve tax advantage. study include two firms ,oil firm and industrial companies firm with limited liability.The inductive method is used for the applied part in analyzing the financial data of the companies considered in 2011-2015.The result of the study shows that the financial leverage achieve present value of the costs is Negative . The study concluded that the most important conclusions of the tax advantage of leverage is higher costs as well as achieving a low tax shield ,This study found out the results that interest payments related to pre-tax all of the loan amount and the percentage of the interest rate on borrowing a direct correlation, in other words, raising the value of the interest rate on borrowing payments before tax when the value of the loan rises and the proportion of the interest rate, and as a result increases the value of what is achieved tax shield for the benefit of the company. Cash flows for the decision to purchase and leverage include (acquisition) cost of interest on the loan and the repayment of the loan value, as well as the costs borne by the company of insurance premiums, maintenance and depreciation costs, a high